Case studies of conservation plans that incorporate geodiversity. Issue 3 (28th April 2015) - Anderson, M. G.; Comer, P. J.; Beier, P.; Lawler, J. J.; Schloss, C. A.; Buttrick, S.; Albano, C. M.; Faith, D. P.
Abstract: Geodiversity has been used as a surrogate for biodiversity when species locations are unknown, and this utility can be extended to situations where species locations are in flux. Recently, scientists have designed conservation networks that aim to explicitly represent the range of geophysical environments, identifying a network of physical stages that could sustain biodiversity while allowing for change in species composition in response to climate change. Because there is no standard approach to designing such networks, we compiled 8 case studies illustrating a variety of ways scientists have approached the challenge. These studies show how geodiversity has been partitioned and used to develop site portfolios and connectivity designs; how geodiversity‐based portfolios compare with those derived from species and communities; and how the selection and combination of variables influences the results. Collectively, they suggest 4 key steps when using geodiversity to augment traditional biodiversity‐based conservation planning: create land units from species‐relevant variables combined in an ecologically meaningful way; represent land units in a logical spatial configuration and integrate with species locations when possible; apply selection criteria to individual sites to ensure they are appropriate for conservation; and develop connectivity among sites to maintain movements and processes. With these considerations, conservationists can design more effective site portfolios to ensure the lasting conservation of biodiversity under a changing climate. Abstract : Estudios de Caso de Planes de Conservación que Incorporan a la Geodiversidad Resumen: La geodiversidad se ha usado como un sustituto de la biodiversidad cuando la ubicación de las especies es desconocida y esta utilidad puede extenderse a situaciones en las que la ubicación de las especies está en cambio constante. Recientemente, los científicos han diseñado redes de conservación que buscan representar explícitamente la gama de ambientes geofísicos, al identificar una red de estados físicos que podrían mantener a la biodiversidad mientras permiten cambios en la composición de las especies en respuesta al cambio climático. Ya que no existe una estrategia estándar para diseñar dichas redes, compilamos ocho estudios de caso que ilustran la variedad de formas con las cuales los científicos han enfrentado el reto. Estos estudios muestran cómo se ha dividido la geodiversidad y cómo se ha usado para desarrollar portafolios de sitios y diseños de conectividad; cómo los portafolios basados en geodiversidad se comparan con aquéllos derivados de las especies y las comunidades: y cómo la selección y la combinación de variables influye sobre los resultados. Colectivamente, los estudios sugieren cuatro pasos clave al usar la geodiversidad para aumentar la conservación basada tradicionalmente en la biodiversidad: crear unidades de suelo a partir de las variables relevantes para las especies combinadas de una forma significativa ecológicamente; representar las unidades de suelo en una configuración espacial lógica e integrarlas con la ubicación de las especies de ser posible; aplicar criterios de selección a los sitios individuales para asegurar que son adecuados para la conservación; y desarrollar la conectividad entre sitios para mantener los movimientos y los procesos. Con estas consideraciones, los conservacionistas pueden diseñar portafolios de sitio más efectivos para asegurar la conservación duradera de la biodiversidad bajo un clima cambiante .